Dakwah Berbasis Masjid: Studi Kasus Masjid Jogokariyan Yogyakarta - Fauzi, Dzulfikar; Muhyani, Muhyani (Komunika: Journal of Communication Science and Islamic Dakwah, 2019)
Da’wah is the duty of every Muslim. The mosque is a means of da’i da’i conveying his da’wah so that the mosque does not only function as a place of worship but also as the centre of Muslim civilization. As in the time of the Prophet Muhammad SAW, the mosque functions for all activities, both worship, social, educational and others. In this study, we want to find out how the efforts made by the administrators of the Jogokariyan Mosque in applying the appropriate da’wah method for the Jogokariyan community. Previously, the Jogokariyan community consisted of the abangan community and the PKI base. This research is field research that directly participates in activities at the Jogokariyan Mosque. From the study results, it appears that the efforts of mosque administrators for mosques from time to time have had a positive impact on the community around the mosque in particular and for outsiders in general. What was once known as a PKI-based village became an Islamic village. Abstrak Dakwah merupakan kewajiban setiap muslim. Masjid merupakan sarana dakwah para da’i menyampaikan dakwahnya. Sehingga masjid bukan hanya berfungsi sebagai tempat ibadah saja, akan tetapi pusat peradaban umat Islam. Sebagaimana di zaman Rasulullah SAW masjid berfungsi untuk semua kegiatan baik ibadah, sosial, pendidikan maupun yang lainnya. Dalam penelitian ini ingin mengetahui bagaimana usaha-usaha yang dilakukan oleh pengurus Masjid Jogokariyan dalam menerapkan metode dakwah yang sesuai untuk masyarakat Jogokariyan. Yang mana dahulunya masyarakat Jogokariyan terdiri dari masyarakat abangan dan basis PKI. Penelitian ini merupakan penelitian lapangan yang langsung turut serta akan kegiatan di Masjid Jogokariyan. Dari hasil penelitian tampak bahwa usaha para pengurus masjid yang dilakukan untuk masjid dari waktu ke waktu telah memberi dampak positif bagi masyarakat sekitar masjid pada khususnya dan bagi masyarakat luar pada umumnya. yang dulu terkenal sebagai kampung yang berbasis PKI menjadi kampung islami.